An upper QoS ontology from service provider’s perspective. - Khanjani, Atieh; Wan Ab. Rahman, Wan Nurhayati (2013)
Quality of service concern is critical and vital to have a successful and high quality web services to satisfy both client and service. In web environment, ontology is not only about the concepts but more than that; it is a clear structure which models the meaning of the knowledge domain. Currently, most of the researches are focusing on improving the quality of web services in terms of user’s perspective while there is a lack of work on provider’s perspective to improve the quality of service in the development phase. This paper proposes an upper QoS ontology from provider’s perspective which aims to be generic and able to be used by any domain.